Twisting of a functionally graded rod with radial gradient - Phang, Francis Ray (Nanyang Technological University, 2023)
The purpose of the Final Year Project is to discover and test the properties of a functionally graded rod. With the different shear and young modulus of different materials, we can study the behaviour and trends when the functionally graded rod undergoes torsion. These materials would be studied under a wide range of gradients characterized by ‘a’ and ‘b’. The displacements are determined from the equilibrium equations and the stresses are subsequently calculated from the displacements. By testing these properties, we could better comprehend these materials, allowing us to have new applications or substitutes with these newly found results.